Pengaruh Kualitas Pelayanan, Kualitas Produk, Dan Suasana Toko Terhadap Keputusan Pembelian Konsumen Pada Toko Cahaya Bulan Di Malang - Alistin, Dita Putri; Salim, Muhammad Agus; Rizal, Mohammad (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
AbstractThis study aims to examine  the influence of service quality, product quality, and store atmosphere on consumer purchasing decisions at Cahaya Bulan building materials store in Malang. The method used is descriptive research analysis with quantitative data. The sample in this study consisted of 100 respondents, selected using purposive sampling technique. The results indicate that service quality, product quality, and store atmosphere have a significant influence on purchasing decisions. Service quality significantly affects purchasing decisions. Product quality significantly affects purchasing decisions. Store atmosphere significantly affects purchasingidecisions.  Keywords: Service Quality, Product Quality, Store Atmosphere, Purchasing Decisions